Effectiveness of problem-based learning models assisted with ethno-fun on learning outcomes reviewed from students' computational thinking - Pertiwi, Hernin Diah Permata; Maharani, Swasti; Darmadi, Darmadi (Universitas Islam Raden Intan Lampung, INDONESIA, 2025)
Purpose: This study aims to evaluate the effectiveness of the Ethnofun-assisted Problem-Based Learning (PBL) model in enhancing student learning outcomes, particularly when viewed through the lens of students’ computational thinking skills. Method: A quantitative research approach was employed using a quasi-experimental design with a Non-Equivalent Groups Factorial Design. The participants consisted of two classes: the experimental group received PBL integrated with Ethnofun, while the control group was taught using the conventional PBL model. Data were analyzed using two-way ANOVA to assess the effect of the learning model and students' computational thinking levels. Findings: The results showed that students who engaged with the Ethnofun-assisted PBL model achieved better learning outcomes compared to those in the conventional PBL class. Additionally, students with higher computational thinking skills demonstrated superior academic performance. However, no significant interaction was found between the learning model and students’ computational thinking levels, indicating that the benefits of the Ethnofun integration were consistent across all categories of computational thinking. Significance: These findings highlight the pedagogical potential of incorporating culturally contextualized media into inquiry-based instruction. Ethnofun not only enriches the learning experience but also supports the development of essential thinking skills, making it a promising tool for fostering deeper understanding and engagement in mathematics education.